Islamic Feminism in India: Indian Muslim Women Activists and the Reform of Muslim Personal Law - SYLVIA VATUK (Modern Asian Studies 42, 2/3 (2008) pp. 489-518, 2007)
I describe here a nascent `Islamic feminist' movement in India, dedicated to the goal of achieving gender equity under Muslim Personal Law. In justifying their demands, these women activists refer neither to the Indian Constitution nor to the universalistic human rights principles that guide secular feminists campaigning for passage of a gender-neutral uniform civil code of personal law, but rather to the authority of the Qur'an-which, they claim, grants Muslim women numerous rights that in practice are routinely denied them. They accuse the male `ulama of foisting `patriarchal' enterpretations of the Qur'an on the unlettered Muslim